1991
DOI: 10.1063/1.461396
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the crystal-field spectra of the actinide tetrafluorides. I. UF4, NpF4, and PuF4

Abstract: An interpretation of the low-temperature absorption spectra of AnF4 (An=U, Np, Pu) is presented. Using an effective operator Hamiltonian with orthogonalized free-ion operators and initializing crystal-field parameter values based on a superposition model calculation for An4+ sites with C2 symmetry, good agreement between the model calculations and experimentally observed absorption band structure could be obtained. Correlations with published magnetic and heat capacity measurements are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 20 publications
11
62
1
Order By: Relevance
“…[4], on the absorption spectrum of U* +. Values of the Marvin radial integrals M h (h = 0, 2, 4) have usually been found to be similar to the HF values in actinides [1] and so they were varied around these values in the optimisation process to achieve the least overall r.m.s. deviation between the experimental and theoretical energies.…”
Section: -Calculations Of Energy Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4], on the absorption spectrum of U* +. Values of the Marvin radial integrals M h (h = 0, 2, 4) have usually been found to be similar to the HF values in actinides [1] and so they were varied around these values in the optimisation process to achieve the least overall r.m.s. deviation between the experimental and theoretical energies.…”
Section: -Calculations Of Energy Levelsmentioning
confidence: 99%
“…Since all the parameters cannot be varied simultaneously and also values of the Marvin radial integrals Mh(h = 0, 2, 4) have usually been found to be similar to the HF values in actinides [1,6] at the values already given and using these ratios, the matrices were diagonalised in which the energy levels became functions of M ~ and a, and were then represented as polynomials cubic in M ~ and a, using Chebyshev double series. The convention adopted was that the coefficients in the summation which have either i or j zero are written as 1/2aij, instead of simply aij, and the coefficient with both i and j equal to zero is written as 1/4a00 In order to maintain the orthogonality of Chebyshev polynomials and hence validity of eq.…”
Section: C) Chebyshev Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional interactions need to be included in the effective Hamiltonian for a more accurate analysis of energy level structures of rare earths [1][2][3][4][5][6][7][8][9]. They are, among others, the higher-order electrostatically correlated perturbations, the dominant being the two-particle[10] and the three-particle (for systems with n t> 3) configuration interactions [ll].…”
Section: -Introductionmentioning
confidence: 99%
“…The orbit-orbit interaction is usually not considered explicitly since its effect can be absorbed into the configuration interaction [3,10]. It has been found [2,7,11] that for a better fit between experiment and theory the smaller but essential contributions of Hss and H~oo need to be considered. Araki in a classic paper [12] suggested that these interactions may have an appreciable effect on the intervals of multiplets in spectra of heavy elements, thus explaining, in part, the deviations from the Land~ interval rule.…”
mentioning
confidence: 99%